Autoimmune Switch of Hashimoto’s thyroiditis to Graves’ Disease: A Rare Case Report - Mahmud, Sujon; Chowdhury, Md Sunny Anam; Hossain, Md Nazmul; Zerin, Fariha; Hasan, Bahalul (Bangladesh Journal of Nuclear Medicine, 2026)
Hashimoto’s thyroiditis and Graves’ disease (GD) represent two ends of the autoimmune thyroid disease spectrum. While progression from GD to Hashimoto’s thyroiditis is relatively common, the reverse transition is rare. We report a case of a 47-year-old woman with long-standing Hashimoto’s thyroiditis and positive anti-thyroid peroxidase antibodies who remained euthyroid on levothyroxine for 10 years. Later, she developed symptoms of thyrotoxicosis, including palpitations, exertional dyspnea, and rapid, unintentional significant weight loss. The reported case demonstrated that the formation of thyroid-stimulating autoantibodies can cause an immunological transition from hypothyroidism to hyperthyroidism, however this is rare. Bangladesh J. Nuclear Med. 28(2): 368-370, 2025